Reporting of Lymph Node Fine Needle Aspiration Cytology by Application of Sydney System and Assessment of Prevalence of Malignancy - Roy, Shriya; Devi, Junu; Kaur, Daljeet (Annals of Pathology and Laboratory Medicine, 2024)
Background: Fine needle aspiration cytology (FNAC) is a stepwise diagnostic approach that combines age, sex, site, clinical findings, multiplicity, ultrasound findings, low power pattern, high power pattern, and disease-specific diagnostic clues, including granulomas. The Sydney System for lymph node cytology classification and reporting has been developed to standardize the reporting language among cytopathologists and clinicians. We aim to apply the proposed Sydney System, categorize lymph node lesions accordingly, and determine the prevalence of different types of malignancies. Materials and Methods: This was a cross-sectional study of lymph node cytology conducted from July 2022 to June 2023 in the Department of Pathology at Gauhati Medical College and Hospital. The results were reported according to the Sydney System into five groups, from L1 to L5. Results: Out of the 555 cases, the cervical group of lymph nodes was the most commonly affected (72.9%). The male-to-female (M:F) ratio was 1.61. The most commonly affected age group was 41-50 years. A total of 54.41% of cases were categorized under L2, followed by 28.29% of cases under L5. Metastatic squamous cell carcinoma (SCC) was the most commonly encountered neoplastic lesion. The prevalence of lymphoma was 2.16% in the present study. The prevalence of malignancy was higher in males compared to females. Conclusion: The Sydney System of reporting and classifying lymph node cytology can help achieve uniformity and reproducibility, leading to fairly accurate risk assessments of malignancy for further clinical management.